MATERIAL DEVELOPMENT OF ENGLISH TEXTBOOK "EFFECTIVE ENGLISH" TO DEVELOP THE STUDENTS’ COMMUNICATIVE COMPETENCE : A CONTENT ANALYSIS - LESTARI, ENDANG (2010)

(untitled)
This research paper is mainly intended to find out to what extend “effective English” English textbook develops the learners’ communicative competence. This research is descriptive qualitative Research. In collecting the data, the writer used documentary analysis especially in content analysis as an instrument. The data where analyze by these steps; (1) Reading the textbook. (2) Accessing to the internet. (3) Arranging the data into several parts according to its classification. (4) Selecting particular parts that are considered important and relevant for the analysis. (5) Drawing conclusion The result of this research indicates that “too much” task are intended to develop linguistic competence (120 tasks). In addition, the writer finds “inadequate” task in actional competence (17 tasks), socio cultural competence (27 tasks) and strategic competence (45 tasks). Its mean that the textbook is not extending task that to develop the learners’ communicative competence. In this study, the writer also finds some aspects of competence are not including in textbook. For example: in linguistic competence there is not morphology’s aspect, in socio cultural competence there are not cultural factor and non verbal communicative factor, and in strategic competence are not Reduction s learners communicative competence strategies, Achievement strategies, and Self-monitoring strategies. This research implies that the textbook entitle “effective English” is not extending to develop the learners communicative competence. So, the task must develop the learners’ communicative competence well